An ion imprinted polymer for the selective extraction of mercury (II) ions in aqueous media - Batlokwa, Bareki Shima (Rhodes University, Faculty of Science, Department of Chemistry, 2010)
This thesis presents the application of an imprinted mercury(lI) polymer that we synthesized by copolymerizing the functional and cross-linking monomers, N'-[3-(Trimethoxysilyl)propyl] diethylenetriamine (TPET) and tetraethylorthosilicate (TEOS) in the presence of mercury (II) ions as template. A bulk polymerization method following a double-imprinting procedure and employing hexadecyltrimethylammonium bromide (CTAB), as a second template to improve the efficiency of the polymer was employed in the synthesis. The imprinted polymer particles were characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and their average size determined by screen analysis using standard test sieves. The relative selective coefficients (k') of the imprinted polymer evaluated from selective binding studies between Hg Â²â ºand CuÂ²â º or HgÂ²â º and CdÂ²â º, were 10588 and 3147, respectively. These values indicated highly favored HgÂ²â º extractions over the two competing ions. Application of the polymer to various real water samples (tap, sea, river, pulverized coal solution, treated and untreated sewerage from the vicinity of Grahamstown in South Africa) showed high extraction efficiencies (EEs) of HgÂ²â º ions; (over 84% in all cases) as evaluated from the detected unextracted HgÂ²â º ions by inductively coupled plasma optical emission spectroscopy (ICP-OES). The limit of detection (LOD, 3Æ¡) of the method was evaluated to be 0.036 ng mlâ »Â¹ and generally the data (n=10) had percentage relative standard deviation (%RSD) of less than 4%. These findings indicate that the double-imprinted polymer has potential to be used as an efficient extraction material for the selective pre-concentration of mercury(lI) ions in aqueous environments.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Mercury; Metal ions; Imprinted polymers; Polymerization